Discovery of new inhibitors of nuclease MRE11 - Nikulenkov, Fedor; Carbain, Benoit; Biswas, Raktim; Havel, Stepan; Prochazkova, Jana; Sisakova, Alexandra; Zacpalova, Magdalena; Chavdarova, Melita; Marini, Victoria; Vsiansky, Vit; Weisova, Veronika; Slavikova, Kristina; et al. (European journal of medicinal chemistry, 2025)
MRE11 nuclease is a central player in signaling and processing DNA damage, and in resolving stalled replication forks. Here, we describe the identification and characterization of new MRE11 inhibitors MU147 and MU1409. Both compounds inhibit MRE11 nuclease more specifically and effectively than the relatively weak state-of-the-art inhibitor mirin. They also abrogate double-strand break repair mechanisms that rely on MRE11 nuclease activity, without impairing ATM activation. Inhibition of MRE11 also impairs nascent strand degradation of stalled replication forks and selectively affects BRCA2-deficient cells. Herein, we illustrate that our newly discovered compounds MU147 and MU1409 can be used as chemical probes to further explore the biological role of MRE11 and support the potential clinical relevance of pharmacological inhibition of this nuclease.
Keywords: Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; objevování léků; BRCA2; nuclease; inhibitory enzymů; MRE11 Homologue Protein; vztahy mezi strukturou a aktivitou; Humans; homologní protein MRE11; MRE11 inhibitor; oprava DNA; molekulární struktura; FEN1; Drug Discovery; DNA Repair; Structure-Activity Relationship; Enzyme Inhibitors; lidé; Molecular Structure